Evaluation of Total Flavonoid Content in Nephelium lappaceum L. Leaves from Different Altitudes Using UV-Vis Spectrophotometry. - Pratiwi, Sekar Ayu; Gobel, Dhea Indira; Kusumaningtyas, Febrianika Ayu (Majalah Farmaseutik, 2025)
Rambutan (Nephelium lappaceum L.) is a widely distributed plant in various regions and is known to contain flavonoid compounds. In pharmaceutical development, the geographical location of plant growth can influence the levels of secondary metabolites. This study aims to determine the total flavonoid content in rambutan leaves based on differences in altitude using UV-Visible spectrophotometry at a wavelength of 435 nm. The leaves were extracted via maceration using ethanol p.a. as the solvent. The total flavonoid content was determined using AlCl₃ reagent with quercetin as the standard. The results showed that rambutan leaves collected from lowland areas (Komo Luar Subdistrict, Wenang District, Manado City) had a higher total flavonoid content (42.7 ppm) compared to those of highland regions (Kampung Jawa Subdistrict, Tomohon City), which contained 30.4 ppm. These findings indicate that plants grown at lower altitudes produce higher levels of flavonoids, possibly due to increased light intensity and climatic conditions, which promote the synthesis of secondary metabolites such as flavonoids.